Obtaining Consensus on Core Clinical Skills for Family Medicine Training - Ian D. Couper; Bob Mash (South African Family Practice)
Background: Family medicine specialist registrar training became a requirement in South Africa in August 2007. As part of the process of developing consensus on the content of training, heads of departments of family medicine agreed to a process for seeking national consensus on the skills required of a graduating family physician. A previously reported research project produced a set of skills lists which were used as the basis for this process.